Smart Phone: a Smart Technology for Fundus Photography in Diabetic Retinopathy Screening - Muhammad Younis Tahir, Fazal Shah Shiraz, Ahmad Zeeshan Jamil, Luqman Ali (Pakistan Journal of Ophthalmology, 2018)
Purpose: To find the reliability of fundus photography using smart phone in diabetic patients compared to Slit lamp biomicroscopic examination. Study design: Comparative cross sectional. Place and Duration of Study: This study was conducted in district headquarter teaching hospital affiliated with Sahiwal Medical College, Sahiwal from January 2017 to December 2017. Material and Methods: 250 eyes of 125 diabetic patients visiting outpatient department were examined for diabetic retinopathy by smart phone fundus photography and slit lamp biomicroscopy b 2 independent ophthalmologiss. Examination was performed after dilatation of the pupil. Diabetic retinopathy changes were noted and graded by each observer for the same patient on a form. Age and gender were recorded for all patients. Results: There was high degree of agreement in findings of the smart phone and the slit lamp which was used as a gold standard. The kappa value was found to be 0.87 between the two methods of diagnosing clinically significant macular oedema (CSME). Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of smart phone fundus photography in diagnosis of CSME was 82.6%, 99.55%, 95%, 98.26% and 98%. Conclusion: Smart phone fundus photography shows reasonable agreement with slit lamp microscopy for the diagnosis of diabetic retinopathy and can be used for the screening purposes. Key words: Diabetic Retinopathy, Macular oedema, Slit Lamp Microscopy, Smart phone, Telemedicine.